Complex noise indicator for noise mapping based on the EU working groups' and Polish results of the annoyance investigations - KUCHARSKI, Radosław (Archives of Acoustics, 2014)
The Noise Directive 2002/49/EU includes obligations for noise mapping for agglomerations above 250 thousand citizens in the first step and later - above 100 thousand people. The noise map of the city consists of, at least, 4 layers of information. Each layer, in graphical form, represents different kinds of noise distribution, for traffic, railway, air and industrial noise.One can ask how to assess the complex exposure for all noises from all layers of the map? The proposition of the complex index evaluation is developed in the paper. At first, it was assumed that the basic indicator for complex description of the acoustic conditions is the sum of the weighted noise exposures connected with the LDWN level from different category of noise. The weights for the complex indicator were worked out on the basis of the results of the noise annoyance investigations, carried out by the European Working Group on health and socio-economic aspects, published in position papers (year 2002 and later).However, one can ask if the European relation between noise levels and noise annoyance is correct for Polish conditions?In the second part of the paper the results of the comparisons between EU's and Polish annoyance curves are presented. The curves were obtained as the correlation's product of the subjective assessments (query) and LDWN levels measurements and calculations. These investigations in Poland were carried out as a part of the annually project called "Noise Monitoring System" (coordinated by Chief Inspectorate of Environmental Protection). Their background results are characterized in the paper.